2019
DOI: 10.1126/scitranslmed.aav0936
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to neoadjuvant chemotherapy in triple-negative breast cancer mediated by a reversible drug-tolerant state

Abstract: Eradicating triple negative breast cancer (TNBC) resistant to neoadjuvant chemotherapy (NACT) is a critical unmet clinical need. In this study, patient-derived xenograft (PDX) models of treatment-naïve TNBC and serial biopsies from TNBC patients undergoing NACT were used to elucidate mechanisms of chemoresistance in the neoadjuvant setting. Barcode-mediated clonal tracking and genomic sequencing of PDX tumors revealed that residual tumors remaining after treatment with standard front-line chemotherapies, doxor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
217
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(242 citation statements)
references
References 56 publications
(79 reference statements)
17
217
0
Order By: Relevance
“…These mechanisms may include activation of drug efflux mechanisms, global expression reprogramming of cancer cells, exhaustion of antitumor immunity, etc. [32][33][34] In conclusion, our study demonstrated plasticity of somatic BRCA1 status during the natural history of BRCA1-driven OC. This plasticity appears to play a central role in determining primary cancer development, response to systemic therapy and subsequent relapse.…”
Section: Discussionsupporting
confidence: 56%
“…These mechanisms may include activation of drug efflux mechanisms, global expression reprogramming of cancer cells, exhaustion of antitumor immunity, etc. [32][33][34] In conclusion, our study demonstrated plasticity of somatic BRCA1 status during the natural history of BRCA1-driven OC. This plasticity appears to play a central role in determining primary cancer development, response to systemic therapy and subsequent relapse.…”
Section: Discussionsupporting
confidence: 56%
“…Triple-negative breast cancer cells have been reported to exhibit genetic and phenotypical shifts in subpopulations, leading to resistance to the available standard drugs [29,30]. However, the functional differences made by genomically heterogeneous triple-negative breast cancer cells to chemoresistance remain poorly understood [31]. Natural ingredients from plants are widely explored to identify their availability for application in patients with breast cancer as an adjuvant approach [32].…”
Section: Discussionmentioning
confidence: 99%
“…8 According to the NACT for breast cancer, the breast-conserving surgery rate is increasing, and the tumor stage is decreasing. 9 Many NACT regimens have been applied to the treatment for breast cancer; however, there are no internationally generally accepted NACT regimens for patients with advanced breast carcinoma. 10 Therefore, it is necessary to look for accurate and sensitive tumor indicators of breast cancer to improve the survival outcome and provide the better prognosis factor for breast cancer.…”
Section: Introductionmentioning
confidence: 99%